Conceptual Approach to Construction of Engineering and Technical Means of Security and Supervision in the Penitentiary System at Present Stage - Andrey BAYBARIN; Alexander GREBENKOV; Vladimir TARYKIN; Gennady PLOHIH (Communications of International Proceedings, 2020)
The article proposes a conceptual approach to the study of the problems of building engineering and technical means of security and supervision (TMOSS) in the context of implementing the tasks of ensuring the safety of facilities and employees at the modern stage of the development of the penal correction system in the context of the application of various forms of innovation: information, organizational, social, technical and technological and co-responsible settlement at the legislative level. The conclusion is made that in the special conditions of the pandemic, the effectiveness of the activities of penitentiary institutions is largely determined by the competence of the penitentiary staff and the effectiveness of the use of modern TMOSS.
Keywords: Penal Correction System; Institution; Employee; Research; Technology; Means; Protection; Supervision; Threat; Safety; System; Analysis; Method; Factor; Program; Concept; Concept; Conceptual Scheme; Development.